FGD Kurikulum Merdeka Belajar dan Capaian Pembelajaran Bahasa Daerah bagi Dosen Undiksha Bali - Hernawan, Hernawan; Haerudin, Dingding; Santosa, Haris; Widyastuti, Temmy; Alamsyah, Zulfikar (Faculty of Language and Literature Education, Universitas Pendidikan Indonesia, 2025)
This community service initiative aims to develop the competencies of Balinese local language teachers regarding the Independent Curriculum through a Focus Group Discussion (FGD). This is critically needed due to challenges stemming from comprehensive changes across all sectors, particularly in the post-Covid-19 pandemic era. The activity involved the participation of local language teachers and lecturers from UNDIKSHA Bali a higher education institution producing graduates in Balinese language education. Thus, it is expected that both lecturers and teachers will comprehend the essence of the Independent Curriculum (Kurikulum Merdeka Belajar) within the context of local language subjects. The initiative commenced with problem identification, followed by developing learning outcomes and formulating well-targeted solutions. After the FGD implementation, lecturers and teachers will be able to execute the Independent Curriculum in Balinese language subjects, particularly at the university level, preparing future graduates to skillfully implement it in their respective schools.